2019
DOI: 10.7759/cureus.5748
|View full text |Cite
|
Sign up to set email alerts
|

Use of Preoperative Radiation Therapy in Early-stage and Locally Advanced Breast Cancer

Abstract: PurposeThere is growing interest in delivering radiation preoperatively (preopRT) rather than postoperatively (postopRT) for breast cancer. Using the National Cancer Database, we evaluated the use and outcomes of preopRT in breast cancer.MethodsWe identified adult females diagnosed with non-metastatic breast cancer treated with definitive surgery and radiation between 2004 and 2014. Logistic regression models evaluated factors associated with use of preopRT in early-stage (clinical T1-3/N0-1) and locally advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Moreover, these patients are more likely to develop T3-T4 tumors, more advanced lymph node disease, and triple-negative subtypes. 24 Prior literature also accentuates the socioeconomic disparities among BC patients, reinforcing these findings. Compared to women of higher socioeconomic status, underprivileged patients are…”
Section: Surgical Practices and Outcomes With Preoperative Radiotherapymentioning
confidence: 67%
See 4 more Smart Citations
“…Moreover, these patients are more likely to develop T3-T4 tumors, more advanced lymph node disease, and triple-negative subtypes. 24 Prior literature also accentuates the socioeconomic disparities among BC patients, reinforcing these findings. Compared to women of higher socioeconomic status, underprivileged patients are…”
Section: Surgical Practices and Outcomes With Preoperative Radiotherapymentioning
confidence: 67%
“…In this study, it was revealed that younger, African American, uninsured, or Medicaid‐insured patients were more likely to undergo preoperative radiotherapy. Moreover, these patients are more likely to develop T3–T4 tumors, more advanced lymph node disease, and triple‐negative subtypes 24 . Prior literature also accentuates the socioeconomic disparities among BC patients, reinforcing these findings.…”
Section: Neoadjuvant Radiotherapymentioning
confidence: 75%
See 3 more Smart Citations